The PDCA Cycle as a Strategic Framework for Enhancing Elementary Literacy: A Case Study of the Class Literacy Tree Intervention in Indonesia - Asep Adang Kurnia; Ahmad Sukandar (CV. Media Digital Publikasi Indonesia, 2026)
This qualitative case study examines the implementation and sustainability of the Class Literacy Tree (POLIKEL) strategy within the One Week One Book (SAMI SAKU) program in Indonesian elementary schools, analyzed through the lens of Deming's Plan-Do-Check-Act (PDCA) management cycle. The research employed a descriptive case study design across two public elementary schools in Sumedang Regency, Indonesia. Data were collected via in-depth interviews, observation, and document analysis, and subsequently analyzed using the interactive model. The findings reveal that while the POLIKEL artifact is a powerful pedagogical tool for promoting reading interest and basic writing skills, its success and sustainability are critically contingent upon the fidelity and integration of the supporting PDCA cycle. Schools that executed a proactive planning (Plan) and a formal evaluation (Check) mechanism achieved continuous, measurable improvement, validating the strategic management framework as essential for scalable pedagogical innovation in resource-constrained educational settings.